Towards coordinated self-organization: An actor-centered framework for the design of disaster management information systems. (December 2020) - Nespeca, V.; Comes, T.; Meesters, K.; Brazier, F.
Abstract: Traditionally, disaster management information systems have been designed to facilitate communication and coordination along stable hierarchical lines and roles. However, to support coordination in disaster response, disaster management information systems need to cater for the emerging roles, responsibilities and information needs of the actors, often referred to as self-organization. To address this challenge, this paper proposes a framework for disaster management information systems that embraces an actor-centered perspective to explicitly support coordination and self-organization. The framework is designed and validated to (i) analyze the current practice of disaster information management, including the way changes occur through self-organization, and (ii) study how to design disaster management information systems that support coordination and self-organization within the current practice. A case study in Jakarta is used to modify and validate the framework, and to illustrate its potential to capture self-organization in practice. The analysis showed that analyzing the actors' activities through the framework can provide insights on the way self-organization occurs. Moreover, networking, preparedness and centralization were found to be key elements in the design of disaster management information systems with an actor-centered perspective.